Hormonal Influences on Cognitive Function - Siti Atiyah, Ali; Tahamina, Begum; Faruque, Reza (Penerbit Universiti Sains Malaysia, 2018)
This article examines how hormonal changes may affect the neuronal networking and mechanisms of cognitive function. Hormones are the chemical regulators of the human body and function critically to maintain various processes, such as growth, emotions and even cognition. Numerous studies have examined the relationship between hormonal effects and cognitive function; these studies have investigated different factors, such as aging, pregnancy, post-natal states, emotions and stress. Different types of hormones produce different outcomes for the human body and mind. Hormones may also contribute to both positive and negative outcomes, depending on whether the hormone levels are too low or too high. To investigate the hormonal effects on cognitive function, the sources of localisation must be localised, so that the neuronal network can be realised. Furthermore, cognitive function does not rely on a specific brain region but is determined by the neuronal network interactions. Thus, it is worthwhile to know the neural mechanisms behind cognitive functions that are affected by hormones.